Impacto das alterações bucais na qualidade de vida de pacientes submetidos à hemodiálise - Silva, Jéssica Antoniana Lira e (2016)
Introduction: Some signs and oral symptoms are often found in hemodialysis patients, and can affect the quality of life of these patients. Objective: Evaluate the impact of oral changes in quality of life for hemodialysis patients. Methodology: This is a cross-sectional study about 226 hemodialysis patients in two hospitals of Brazilian Health Unic System (SUS) in the city of Campina Grande-PB. Patients answered a socioeconomic, demographic and clinical questionnaire, underwent an intraoral physical examination, which was carried out by a properly calibrated examiner, then was held the interview in which was filled in the quality of life questionnaire Oral Health Impact Profile (OHIP-14). Statistical analysis considered a significance level of 5% and used the segmentation technique (K-means Cluster) in order to get three clusters of patients with different levels of impact on oral health-related quality of life (OHRQoL). For evaluating the association between the dependent variable and the independent variables was used multivariate analysis using a decision tree through the CHAID algorithm (Chi-squared Automatic Interaction Detector) and subsequently ordinal logistic regression. Results: Three clusters were formed considering the impact on oral health-related quality of st nd life: 1 cluster (n=92; 40.7%) - individuals with low impact; 2 cluster (n=74; 32.7%) - average rd impact individuals and 3 cluster (n=60; 26.5%) - individuals with high impact. The averages for all areas of the OHIP-14 range between 0.10 and 2.54. Patients older than 57 years (OR = 2.35; 95% CI: 1.42 to 3.87; p = 0.001), toothache report in the last 6 months (OR = 2.40; 95%: 1.26 to 4.58; p = 0.008) and those living in rural areas (OR = 2.43; 95% CI: 1.13 to 5.23; p = 0.023) were more likely to exhibit a greater impact on OHRQoL. Conclusion: Oral diseases don’t cause a high impact on QVRSB of hemodialysis patients. Factors associated with greater impact were toothache report in the last 6 months older than 57 years old and reside in rural areas.